2021
DOI: 10.1523/jneurosci.2249-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Causally Contributes to Vocabulary Translation following Sensorimotor-Enriched Training

Abstract: The role of the motor cortex in perceptual and cognitive functions is highly controversial. Here, we investigated the hypothesis that the motor cortex can be instrumental for translating foreign language vocabulary. Human participants of both sexes were trained on foreign language (L2) words and their native language translations over 4 consecutive days. L2 words were accompanied by complementary gestures (sensorimotor enrichment) or pictures (sensory enrichment). Following training, participants translated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…It not only improves children’s motor-learning abilities, performance, and tolerance, but it also aids in the rehabilitation of children with cerebral palsy and developmental delay [ 41 ]. Furthermore, based on the evidence, TMS has potential benefits for fine-motor-skills rehabilitation in CP [ 42 ], induces foreign language learning within the primary motor cortex, and has behavioral benefits [ 43 ]. Overall, VR, tDCS, and TMS have the potential to be promising technological tools for children with motor deficits, even though the underlying brain mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It not only improves children’s motor-learning abilities, performance, and tolerance, but it also aids in the rehabilitation of children with cerebral palsy and developmental delay [ 41 ]. Furthermore, based on the evidence, TMS has potential benefits for fine-motor-skills rehabilitation in CP [ 42 ], induces foreign language learning within the primary motor cortex, and has behavioral benefits [ 43 ]. Overall, VR, tDCS, and TMS have the potential to be promising technological tools for children with motor deficits, even though the underlying brain mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that the motor system could be involved in action-verb encoding and representation. More recently, Mathias et al (2021) employed another neuromodulation protocol: offline, inhibitory continuous theta burst stimulation (cTBS) combined with repetitive TMS (rTMS). The experiment involved sensorimotor-enriched training for foreign-language learning.…”
Section: Relationship Between the Motor And Language Systemmentioning
confidence: 99%
“…The mechanisms underlying these learning effects are not yet well understood. One candidate mechanism may be motor-to-sensory predictions: performing movements is thought to elicit predictions of resulting sensory feedback (Mathias et al, 2021 ; Miall & Wolpert, 1996 ). Because accurate prediction depends on prior learning (Bar, 2007 ; Bubic et al, 2010 ), the benefit of movement on encoding may also depend on experience.…”
Section: Introductionmentioning
confidence: 99%
“…One such robust phenomenon in the language domain, known as the production effect , occurs when participants first study lists of words by speaking them out loud or silently reading (or hearing) them, and subsequently show increased recognition accuracy for the spoken words compared to the silently studied words (Forrin et al, 2012 ; MacLeod et al, 2010 ; Mama & Icht, 2016 ; Murray, 1965 ; Ozubko et al, 2012 ). Notably, other types of production (i.e., movement) such as writing, typing, whispering, and gesturing, also appear to benefit word recognition compared to perceptual learning conditions involving either reading or hearing words (Forrin et al, 2012 ; Mama & Icht, 2016 ; Mathias et al, 2021 ). Movement has also been associated with memory enhancements in other contexts, involving different types of movements when learning different types of items.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation